2019
DOI: 10.18087/cardio.2019.2.10227
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Function of the Left Heart Myocardium by Tissue Doppler Imaging and Speckle Tracking Echocardiography in Patients with Chronic Heart Failure with Preserved Left Ventricular Ejection Fraction

Abstract: Aim:to study myocardial function in patients with chronic heart failure (CHF) with preserved left ventricular ejection fraction (PEF) by speckle tracking echocardiography and tissue doppler imaging.Materials and methods.We examined 80 patients aged 50–70 years with verified NYHA class I–IIa CHF and PEF due to arterial hypertension and ischemic heart disease, and 35 healthy persons. Examination included echocardiography, and speckle-tracking echocardiography.Results.According to 6-min walk test 26.9 % of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(9 reference statements)
0
1
0
1
Order By: Relevance
“…It has been reported that the current survival rate of CHF with multiple causes is comparable to that of patients with malignant neoplastic diseases, with a high mortality rate exceeding 50% [ 15 ]. However, conventional diagnosis fails to provide a comprehensive analysis of the cardiac function, resulting in a high risk of misdiagnosis and underdiagnosis, along with the invasiveness of many examinations, which prevents desirable diagnostic results [ 16 , 17 ]. Ultrasound technology has been widely used in clinical practice, and cardiac ultrasound provides a comprehensive evaluation of the cardiac function by effectively displaying detailed information such as cardiac data and blood flow data of the examined subjects.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the current survival rate of CHF with multiple causes is comparable to that of patients with malignant neoplastic diseases, with a high mortality rate exceeding 50% [ 15 ]. However, conventional diagnosis fails to provide a comprehensive analysis of the cardiac function, resulting in a high risk of misdiagnosis and underdiagnosis, along with the invasiveness of many examinations, which prevents desirable diagnostic results [ 16 , 17 ]. Ultrasound technology has been widely used in clinical practice, and cardiac ultrasound provides a comprehensive evaluation of the cardiac function by effectively displaying detailed information such as cardiac data and blood flow data of the examined subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Показано, что показатели продольной деформации ЛЖ коррелируют с величиной ФВ ЛЖ, что находит подтверждение в результатах настоящего исследования, но при этом являются более ранними предикторами снижения сократительной способности миокарда. Кроме того, ухудшение показателей продольного стрейна рассматривается как предиктор прогрессирования сердечной недостаточности [22].…”
Section: Discussionunclassified